2012
DOI: 10.1037/a0029783
|View full text |Cite
|
Sign up to set email alerts
|

Mindsets and human nature: Promoting change in the Middle East, the schoolyard, the racial divide, and willpower.

Abstract: Debates about human nature often revolve around what is built in. However, the hallmark of human nature is how much of a person's identity is not built in; rather, it is humans' great capacity to adapt, change, and grow. This nature versus nurture debate matters-not only to students of human nature-but to everyone. It matters whether people believe that their core qualities are fixed by nature (an entity theory, or fixed mindset) or whether they believe that their qualities can be developed (an incremental the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
212
0
9

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 342 publications
(228 citation statements)
references
References 62 publications
7
212
0
9
Order By: Relevance
“…Many studies have demonstrated a relationship between a growth mindset and achievement (Aronson et al, 2002;Blackwell, 2007;Burnett et al, 2013;Cury et al, 2008;Devers, 2015;Dweck et al, 2000;2012;Good, 2003;Stipek et al, 1996;Tirri & Kujala, 2016;Yeager & Walton, 2011;Zeng et al, 2016). Growth mindset appears to have a direct positive impact on students' academic achievement throughout primary and secondary schools.…”
Section: Mindset and Achievementmentioning
confidence: 99%
“…Many studies have demonstrated a relationship between a growth mindset and achievement (Aronson et al, 2002;Blackwell, 2007;Burnett et al, 2013;Cury et al, 2008;Devers, 2015;Dweck et al, 2000;2012;Good, 2003;Stipek et al, 1996;Tirri & Kujala, 2016;Yeager & Walton, 2011;Zeng et al, 2016). Growth mindset appears to have a direct positive impact on students' academic achievement throughout primary and secondary schools.…”
Section: Mindset and Achievementmentioning
confidence: 99%
“…In addition to competence-based motive dispositions (i.e., need for achievement, fear of failure), future research could examine a number of other antecedents of individuals' achievement goals and underlying reasons, such as the type of implicit theory of intelligence people hold (Dweck, 2012;Dweck & Leggett, 1988). When people hold an entity theory, they believe their intelligence is set by nature.…”
Section: Reasons Underlying Achievement Goalsmentioning
confidence: 99%
“…In the present study, for the sake of convenience and uniformity, the term "mindset" will be used. Previous reviews examining the relationship between students' mindsets and their performance indicate that mindset has an essential role in learning (Burnette, O'Boyle, VanEpps, Pollack, & Finkel, 2013;Dweck, 2000Dweck, , 2012Tirri & Kujala, 2016;Yeager & Walton, 2011). Dweck and Leggett's (1988) social-cognitive approach to motivation and personality specified how individuals' implicit theories oriented them to set different goals and influenced their perceived ability, their cognitive and affective mechanisms, and their behavior patterns.…”
Section: Introductionmentioning
confidence: 99%
“…Dweck's (2000) review of findings based on her 30 years' research illustrated that people's implicit theories not only affected their self-judgment and played an important role in their adaptive or maladaptive functioning, but also affected the way in which they judged and treated others. Dweck's (2012) later research indicated that a growth mindset could "advance conflict resolution between longstanding adversaries, decrease even chronic aggression, foster cross-race relations, and enhance willpower" (p. 614). By introducing the SOMA (setting/operating/monitoring/achievement) model into a quantitative synthesis of research collected from the year 1988 to 2010, Burnette, O'Boyle, VanEpps, Pollack, and Finkel's (2013) meta-analysis demonstrated that implicit theories predicted selfregulatory process, which in turn, predicted goal achievement.…”
Section: Introductionmentioning
confidence: 99%